MINIMALLY INVASIVE OSTEOSYNTHESIS WITH PLATE OR NAIL FOR META-DIAPHYSEAL TIBIAL FRACTURES - WHAT IS BETTER? - B. Makelov (Trakia Journal of Sciences)
The aim of this article is to review the surgical techniques for minimally invasive osteosynthesis and associated complications with application of locking compression plates, which have undeniable biomechanical and biological advantages in the treatment of multifragmentary meta-diaphyseal tibial fractures. Unstable proximal tibial fractures include a vast majority of fracture patterns affecting the lower extremities. Most of the fracture types are as a result of high-energy trauma from car accidents, high-altitude injury or motor vehicle incident. Usually, those fractures present with severe soft tissue injury with varying degrees of intra-articular fracture involvement. Intramedullary nailing of tibial fractures as a proven method of biologic fixation and represents one of the most widely used methods for the treatment of unstable fractures involving the proximal meta-diaphyseal area of the tibia, allowing sufficient fracture stability during the early limb movement and weight bearing on the leg. Nevertheless, the complications and technical difficulties in its application raise the question for the choice of an appropriate implant in the treatment of these fracture models in terms of their morphology. Minimally invasive percutaneous plate osteosynthesis with indirect reduction and biologic fixation has the advantage of spearing the local blood flow, even in severely comminuted tibial fracture patterns. The use of pre-contoured locking compression plates for proximal tibia allows stable fixation with good and excellent final clinical results.